GliderTools: A Python Toolbox for Processing Underwater Glider Data - Gregor, Luke; Ryan-Keogh, Thomas J.; Nicholson, Sarah-Anne; du Plessis, Marcel; Giddy, Isabelle; Swart, Sebastiaan (Frontiers in Marine Science, 2019)
Underwater gliders have become widely used in the last decade. This has led to a proliferation of data and the concomitant development of tools to process the data. These tools are focused primarily on converting the data from its raw form to more accessible formats and often rely on proprietary programming languages. This has left a gap in the processing chain for glider data, specifically academics, who often need to perform secondary quality control, calibrate, correct, interpolate and visualise data. Here, we present GliderTools, an open-source Python package that addresses these needs of the glider user community. The tool is designed to change the focus from the processing to the data. In this paper, we present a set of tools, that includes: secondary cleaning and calibration, calibration procedures for bottle samples, fluorescence quenching correction, photosynthetically available radiation corrections and data interpolation in the vertical and horizontal dimensions. Many of these processes have been described in several other studies, but do not exist in a collated package designed for underwater glider data. Importantly, we provide potential users with guidelines on how these tools are used so that they can be easily and rapidly accessible to a wide range of users that span the student to the experienced researcher. We recognise that this package may not be all-encompassing for every user and we thus welcome community contributions and promote GliderTools as a community-driven project for scientists.